Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1113/jp270446
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of sarcoplasmic reticulum Ca2+ release in heart failure through mechanical intervention

Abstract: Left ventricular assist devices (LVADs) were developed as a means of temporary circulatory support, but the mechanical unloading they offer also results in significant reverse remodelling. In selected patients, these improvements are sufficient to allow ultimate device explantation without requiring transplantation; this represents a fundamental shift in our understanding of heart failure. Like heart failure itself, LVADs influence multiple biological systems. The transverse tubules are a system of membrane in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…First, they support our main thesis that cardiac atrophy is the most serious harmful effect of prolonged mechanical unloading which, even in the face of the sound evidence on molecular and structural ‘reverse remodeling’ after LVAD application [ 4 , 6 , 11 , 15 , 30 ], could limit successful outcomes of such treatment in terms of functional cardiac recovery and possible weaning from LVAD treatment.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…First, they support our main thesis that cardiac atrophy is the most serious harmful effect of prolonged mechanical unloading which, even in the face of the sound evidence on molecular and structural ‘reverse remodeling’ after LVAD application [ 4 , 6 , 11 , 15 , 30 ], could limit successful outcomes of such treatment in terms of functional cardiac recovery and possible weaning from LVAD treatment.…”
Section: Discussionsupporting
confidence: 61%
“…Unfortunately, prolonged LVAD support was reported to induce cardiac atrophy, probably the main harmful effect in such treated patients. Most probably, cardiac atrophy underlies the lack of significant myocardial function improvement in LVAD patients, even though their hearts exhibit molecular, functional, and structural signs of reverse remodeling [ 4 , 6 , 11–15 ]. None of the approaches aimed at minimizing this detrimental effect proved successful.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the diet-induced increases in myocardial concentration of myristic, palmitic and palmitoleic acids did not alter the pattern of the LV gene expression, similarly in healthy and failing hearts after HT x . This is important because, initially, after the discovery that the remodeling process of the atrophied or hypertrophied heart includes a return to the "fetal gene program" (Depre et al 1998, Depre et al 1999, Taegtmeyer et al 2010, the dominant view has been that a return to the fetal gene program is detrimental and a hallmark of progressive deterioration in cardiac functions (Bloomekatz et al 2016, Ibrahim et al 2015, Soppa et al 2008. In accordance with this claim it was even distinguished between "physiological" and "pathological" hypertrophy (Dorn 2007, Lee et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…in patients with advanced HF waiting for cardiac transplantation (Braunwald 2015, Drakos et al 2016, McLarty 2015. Until recently it was believed that adverse cellular, structural and functional changes in the myocardium of patients with HF ("remodeling process"), are progressive and irreversible (Braunwald 2015, Ibrahim et al 2015. However, this belief has been shown to be inaccurate, Vol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation